PEMBERIAN PUPUK KANDANG SAPI DAN POC NASI BASI DALAM PENINGKATAN KESUBURAN TANAH PADA GRAFTING TANAMAN ANGGUR (Vitis vinifera) DI PRE NURSERY - Saragih, Mhd Yazid Majdiy; Tarigan, Ruth Riah Ate; Ginting, Orleans (Fakultas Pertanian, Universitas Janabadra, 2024)
The aim of this research is to determine the application of cow manure and stale rice POC in increasing soil fertility in grafting grape plants (vitis vinifera) in the pre-nursery. This research used a factorial randomized block design (RAK) consisting of 2 factors with 12 treatment combinations and 3 replications so that 36 plots were needed in the research. The first factor studied was the treatment of cow manure with the symbol